2023
DOI: 10.1002/phar.2856
|View full text |Cite
|
Sign up to set email alerts
|

Empiric dosing strategies to predict lamotrigine concentrations during pregnancy

Abstract: IntroductionMaintaining seizure control with lamotrigine is complicated by altered pharmacokinetics and existence of subpopulations in whom clearance increases or remains constant during pregnancy.ObjectiveOur objective was to characterize the potential for particular dosing scenarios to lead to increased seizure risk or toxicity.MethodsLamotrigine pharmacokinetic parameters obtained from our previous study were applied to a one‐compartment model structure with subpopulations (75:25%) exhibiting different clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The current study by Barry et al 5 adds to previous simulation reported by Pa et al, 6 which evaluated a single scenario of LTG dose increase regimen (25, 50, and 25 mg per dose for each subsequent trimester) from a preconception dose of 150 mg twice daily (thus, 175 mg, 225 mg, and 250 mg twice daily) and assuming equal clearance rate changes for all simulated pregnancies, as sufficient dose increments to maintain the target LTG serum concentrations. 6 Barry and colleagues simulate, at individual and population levels, various LTG dose adjustment regimens (no-change, double-dose, 25 mg every 2 weeks, 25 mg every 4 weeks, 50 mg every 4 weeks, 100 mg every 4 weeks) to LTG-exposed pregnancies from the 2 known subpopulations of clearance (high and low change) starting from different preconception daily doses (100 mg, 200 mg, 300 mg, 400 mg).…”
Section: Commentarymentioning
confidence: 61%
See 4 more Smart Citations
“…The current study by Barry et al 5 adds to previous simulation reported by Pa et al, 6 which evaluated a single scenario of LTG dose increase regimen (25, 50, and 25 mg per dose for each subsequent trimester) from a preconception dose of 150 mg twice daily (thus, 175 mg, 225 mg, and 250 mg twice daily) and assuming equal clearance rate changes for all simulated pregnancies, as sufficient dose increments to maintain the target LTG serum concentrations. 6 Barry and colleagues simulate, at individual and population levels, various LTG dose adjustment regimens (no-change, double-dose, 25 mg every 2 weeks, 25 mg every 4 weeks, 50 mg every 4 weeks, 100 mg every 4 weeks) to LTG-exposed pregnancies from the 2 known subpopulations of clearance (high and low change) starting from different preconception daily doses (100 mg, 200 mg, 300 mg, 400 mg).…”
Section: Commentarymentioning
confidence: 61%
“…Threshold for efficacy risk was set at 65% lower than preconception LTG serum concentrations and threshold for toxicity was set as twice the preconception concentrations. 5 All 24 dose adjustment scenarios predicted lower than 65% preconception concentration (and risk of seizures) at 3 to 26 weeks' gestation in the high change group, whereas this was observed only in the no-change regimen in the low change group, late in the pregnancy. With LTG dose unchanged in the high clearance change group, 65% lower than preconception LTG levels are expected as early as 6 to 8 weeks, with risk of seizures of 7% to 100% depending on preconception dose.…”
Section: Commentarymentioning
confidence: 93%
See 3 more Smart Citations